The Importance of Needs Analysis in a Language Curriculum Development: An Evaluation to 2013 Curriculum - Sulistyani, Ummi Nur Laila (UICELL, 2018)
Improving the quality of education is one important point planned by Indonesian government. In order to achieve the good quality of education, Indonesian educational system has set the goal to be achieved; as written in Indonesian constitution number 20, year 2003. To achieve the national educational goals set by Indonesian government, curriculum should be arranged and formulated strategically into certain programs. In the process of developing a language curriculum, needs analysis take a big part in setting the result to be achieved by the learners. Needs analysis in language curriculum development is defined as the process of determining the needs for which a learner or group of learners requires a language and arranging the needs according to priorities. Needs analysis is normally required before syllabus can be developed for language teaching. The study attempts to investigate the role of needs analysis in a language curriculum design and materials development. It will also discuss about managing the needs analysis in classrooms and procedures for conducting needs analysis.